The ERAP2 gene is associated with preeclampsia in Australian and Norwegian populations - Johnson, M.; Roten, L.; Dyer, T.; East, C.; Forsmo, S.; Blangero, J.; Brennecke, S.; Austgulen, R.; Moses, Eric (2009)
Preeclampsia is a heritable pregnancy disorder that presents new onset hypertension and proteinuria. We have previously reported genetic linkage to preeclampsia on chromosomes 2q, 5q and 13q in an Australian/New Zealand (Aust/NZ) familial cohort. This current study centered on identifying the susceptibility gene(s) at the 5q locus. We first prioritized candidate genes using a bioinformatic tool designed for this purpose. We then selected a panel of known SNPs within ten prioritized genes and genotyped them in an extended set of the Aust/NZ families and in a very large, independent Norwegian case/control cohort (1,139 cases, 2,269 controls). In the Aust/NZ cohort we identified evidence of a genetic association for the endoplasmic reticulum aminopeptidase 1 (ERAP1) gene (rs3734016, Puncorr = 0.009) and for the endoplasmic reticulum aminopeptidase 2 (ERAP2) gene (rs2549782, Puncorr = 0.004). In the Norwegian cohort we identified evidence of a genetic association for ERAP1 (rs34750, Puncorr = 0.011) and for ERAP2 (rs17408150, P uncorr = 0.009). The ERAP2 SNPs in both cohorts remained statistically significant (rs2549782, Pcorr = 0.018; rs17408150, Pcorr = 0.039) after corrections at an experiment-wide level. The ERAP1 and ERAP2 genes encode enzymes that are reported to play a role in blood pressure regulation and essential hypertension in addition to innate immune and inflammatory responses. Perturbations within vascular, immunological and inflammatory pathways constitute important physiological mechanisms in preeclampsia pathogenesis. We herein report a novel preeclampsia risk locus, ERAP2, in a region of known genetic linkage to this pregnancy-specific disorder.